DETEKSI CLOSTRIDIUM DIFFICILE TOKSIGENIK MENGGUNAKAN UJI CEPAT TOKSIN DAN REAL TIME POLYMERASE CHAIN REACTION (Toxigenic Clostridium Difficile Detection Using Toxin Rapid Test and Real Time Polymerase Chain Reaction) - Ika Yasma Yanti; Dalima Ari Wahono Astrawinata (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Toxigenic Clostridium difficile infection, causing a Pseudo Membrane Colitis (PMC) and Clostridium Difficile Associated Diarrhea(CDAD) has increased sharply. The largest risk factor is the use of antibiotics. The purpose of this study was to know how to determinethe prevalence and characteristics of subjects with Toxigenic Clostridium difficile and to assess the ability of the toxin rapid test comparedto real-time PCR. Ninety adult subjects with antibiotic therapy more than two (2) weeks were enrolled in this study. The results of toxinrapid test and real-time PCR were presented in a 2x2 table, statistical test used was Chi square. The prevalence of Toxigenic Clostridiumdifficile based on the toxin rapid test and by real-time PCR was 27.3% and 37.5%, respectively. There were significant differences betweenstool consistency and number of antibiotics used with the detection of Toxigenic Clostridium difficile. There was a relationship betweenthe duration of antibiotic therapy with the detection of Toxigenic Clostridium difficile using real-time PCR (p=0.010, RR=2.116). Thesensitivity, specificity, PPV, NPV, PLR and NLR rapid test against real-time PCR were 69.7%; 98.2%; 95.8%; 84.4%; 39.2 and 0.31,respectively. This study concluded that the prevalence of Clostridium difficile in RSCM was higher compared to that in Malaysia, Thailandand India; the subjects with antibiotic therapy for more than four (4) weeks had a double risk to have Toxigenic Clostridium difficilethan subjects with antibiotic therapy for less than that time (4 weeks). Thus, in this study, toxin rapid test could be used as a tool todetect Toxigenic Clostridium difficile.